Identification of Technological Pedagogical Content Knowledge of Pre-Service Teacher in English Language Learning - Wahab, Aulia Dwi Amalina; Nurhasanah; Abdul Kadir Jaelani; Baiq Nada Buahana (Universitas Lancang Kuning, 2024)
This study aims to identify the competencies of prospective early childhood teachers in integrating Technological Knowledge (TK), Pedagogical Knowledge (PK), Content Knowledge (CK), Technological Pedagogical Knowledge (TPK), Technological Content Knowledge (TCK), Pedagogical Content Knowledge (PCK), and Technological Pedagogical Content Knowledge (TPACK). This study uses a descriptive method and data is collected through a structured questionnaire. The sample consisted of 20 students from the Early Childhood Teacher Education Study Program, class of 2021. The results of the study show that high performance in TPACK with the